Concept Analysis of Managerial Supervision, Academic Supervision, Clinical Supervision Studies in Educational Institutions - Wahyudin, Achmad; Supardi; Nugraha, Enung (Journal of Educational Analytics, 2024)
The stage in searching some literature using a search engine or maybe easier is indexing any type of document. Sentences with a list of documents related to the keywords concept, managerial supervision, academic supervision, clinical supervision and educational institution. The steps taken in this study are by identifying data that has a correlation with the research theme in the form of books or articles or journals. This article discusses the management of managerial supervision, academic supervision, clinical supervision in educational institutions. Superintendents and principals carry out supervision in schools in essence providing assistance aimed at improving and fostering aspects of learning so as to understand the wider educational environment so that it can be assumed that school supervision covers all functions and issues related to improving teacher professionalism. The purpose of supervision is to provide services and assistance to improve the quality of teacher teaching in the classroom which in turn to improve the quality of student learning.